Factors Influencing Young Consumers of Organic Food Products to Lead a Healthy Lifestyle - Jose, Heerah; Koshy, Moli P. (Indian Journal of Marketing, 2018)
Our society's concept of healthy lifestyle is limited to eating fruits and vegetables regularly ; however, when these items are filled with pesticides, rather than having a positive impact, it will adversely affect our health in the long run. Therefore, it is vital to know the attitude of young consumers towards organic food products. There is a high chance for beliefs and habits developed at a young age to prolong, thus giving this study its impetus to take place. Using the purposive sampling technique, 112 respondents (young college students) between the age group of 20 - 24 years participated in the study. Throughout the literature on buying of organic food products, the concept of fear and food safety concern has been treated as one construct, however, there are studies which stated that they can be treated as different. Along with that, a positive attitude does not lead to positive behaviour due to various influences from the environment. The present study found that both fear and food safety concern acted as a catalyst to motivate individuals to form a positive attitude towards organic food products to lead a healthy lifestyle. However, the interaction effect of social pressure had a higher chance of increasing the healthy lifestyle of an individual.